New laws of robotics : defending human expertise in the age of AI - Pasquale, Frank (The Belknap Press of Harvard University Press, 2020)
AI threatens to disrupt the professions as it has manufacturing. Frank Pasquale argues that law and policy can avert this outcome and promote better ones: instead of replacing humans, technology can make our labor more valuable. Through regulation, we can ensure that AI promotes inclusive prosperity.